Hypertext: Origins and use - Ellis, David (International journal of information management, 1991)
This paper is intended to provide a brief introduction to the concept of hypertext illustrated with examples from experimental and operational systems. The origins of the hypertext concept are described and different generic types of hypertext systems outlined. The potential and problems of hypertext are discussed with particular reference to information retrieval.